Preventive effect of Shuidouchi (short-term fermented soybean) on dextran sulfate sodium (DSS)-induced colitis in mice - Tan Fang; Liao Wei; Zhao Xin (E3S Web of Conferences, 2019)
In this study, mice colitis model was induced by dextran sodium sulfate (DSS), and the preventive effect of Shuidouchi on colitis was observed. The mice were divided into normal group, model group, low-content Shuidouchi feeding group, high-content Shuidouchi feeding group and sulfasalazine group. Serum and colon tissues of mice were detected by endothelin-1 (ET-1), somatostatin (SS), substance P (SP), vasoactive intestinal peptide (VIP), myeloperoxidase (MPO), glutathione (GSH), malondialdehyde (MDA), superoxide dismutase (SOD), interleukin-2 (IL-2), interleukin-10 (IL-10) kits. The results showed that compared with the model group, the feeding of Shuidouchi could significantly increase the length of colon and the ratio of colon weight to colon length in colitis mice (p < 0.05). By feeding Shuidouchi, the serum levels of ET, SP, IL-10 were decreased and SS, VIP, IL-2 were increased in mice with colitis. Detection of colon tissue in mice showed that Shuidouchi could significantly increase the levels of GSH, SOD and decrease the MPO, MDA levels in colitis mice (p < 0.05). It can be seen from this that Shuidouchi has a good preventive effect on colitis.